In vitro Antimicrobial Susceptibility of Urinary Tract Infection Pathogens in Children - Sevgin Taner; Sabire Şöhret Aydemir; Su Özgür; Ezgi Aksoy; Ahmet Keskinoğlu; Alper Tünger; Caner Kabasakal; İpek Kaplan Bulut (Galenos Yayinevi, 2023)
Aim:Urinary tract infection (UTI) is one of the most common bacterial infections in children. Empirical treatment is commenced according to the patient's characteristics and the antimicrobial susceptibility patterns in the region. Therefore, a determination of antimicrobial resistance patterns has a great importance in effective treatment. The aim of this study was to determine the pathogens which cause UTIs in patients admitted to a university hospital in Izmir and to determine their antimicrobial susceptibility pattern.Materials and Methods:The files of patients aged between 0-18 years, followed up with a diagnosis of UTI, vesicoureteral reflux and neurogenic bladder in Ege University Faculty of Medicine Paediatric Nephrology Unit between February, 2013 and November, 2018 were retrospectively reviewed.Results:A total of 1,126 positive urine cultures from 729 patients (65% female) were included in this study. Gram-negative pathogens constituted 88.2% of the cultures. Escherichia coli (E. coli) was the most commonly isolated bacteria with a prevalence of 59.1%, followed by Klebsiella pneumonia with 17.9%, and Enterococcus faecalis with 8.3% (n=93). Ampicillin, cefuroxime and trimethoprim-sulfamethoxazole with susceptibility rates of 18.6%, 39.6%, 49.0% respectively, constituted the highest resistant antimicrobials to Enterobacteriaceae. Enterococcus spp. showed the highest resistance to gentamycin with 50% resistance in tested cases. Pseudomonas spp. with 64.3% susceptibility showed the highest resistance to piperacillin-tazobactam.Conclusion:This study revealed that bacterial resistance to commonly used antimicrobials in UTI is an important and challenging problem which requires planning.